Comparison of the anthropometric: weight, height and BMI the athletes the Santos football club professional and sub-20. - Rosa, Alex Sandro Pedro (2012)
The goal of study was to compare the anthropometric profile. The research was descriptive sample was group professional = 38 athletes 17 and 35 years old, and group sub-20 = 38 athletes 17 and 20 years old. In this study, it was e evaluated the weight, the height and the (BMI).The results showed two groups of athletes, the variables of weight, height, BMI, very homogeneous, they did not show statistically significant in results between the players of the professional and sub-20categories Santos FootballClub. The only variable that showed differences statistically significant between the two groups was the height.